PEMBINAAN KOMPETENSI PROFESIONAL GURU OLEH KEPALA SEKOLAH PADA SMP NEGERI 2 KOTA SIGLI - Aminah .; Khairuddin .; Muhammad Husen (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2012)
Abstract: Coaching of teachers is one form of business to enhance the professional competence of teachers in achieving quality learning period on SMP Negeri 2 Sigli. This study aims to determine teacher training in: (1) the process of preparing the learning program are: curriculum, syllabus, lesson plans, annual program, the semester program, and details of the effective week. (2) fostering the implementation of learning, namely: the initial activity to open the lesson, explaining the materials, instructional media, learning methods, learning resources, and KKM. (3) fostering enhancement of professional competence of teachers are: supervision, refresher courses, seminars, and MGMP. The method used in this research is descriptive method with qualitative approach, this research sites in SMP Negeri 2 Sigli. Data collection techniques in the study carried out directly by the researcher through interviews, observation, and study documentation. The subject of this research is the principal, vice principal areas of the curriculum, and teacher SMP Negeri 2 Sigli. The results obtained are: (1) principals in the process of preparing teachers to foster learning programs such as the RPP, the annual program, the semester program, and details of the effective week. (2) fostering the principal teachers in the implementation of the learning done by describing the materials, instructional media, learning methods, learning resources. (3) school head teachers to foster improvement of professional competence by way of supervision, Panataran, seminars and enable MGMP as well as providing facilities and infrastructure.Key words: development of professional competence ofteachers